Nodal dependent differential localisation of dishevelled-2 demarcates regions of differing cell behaviour in the visceral endoderm - Trichas, G; Joyce, B; Crompton, L; Wilkins, V; Clements, M; Tada, M; Rodriguez, T; Srinivas, S (Public Library of Science, 2011)
The anterior visceral endoderm (AVE), a signalling centre within the simple epithelium of the visceral endoderm (VE), is required for anterior-posterior axis specification in the mouse embryo. AVE cells migrate directionally within the VE, thereby properly positioning the future anterior of the embryo and orientating the primary body axis. AVE cells consistently come to an abrupt stop at the border between the anterior epiblast and extra-embryonic ectoderm, which represents an end-point to their proximal migration. Little is known about the underlying basis for this barrier and how surrounding cells in the VE respond to or influence AVE migration. We use high-resolution 3D reconstructions of protein localisation patterns and time-lapse microscopy to show that AVE cells move by exchanging neighbours within an intact epithelium. Cell movement and mixing is restricted to the VE overlying the epiblast, characterised by the enrichment of Dishevelled-2 (Dvl2) to the lateral plasma membrane, a hallmark of Planar Cell Polarity (PCP) signalling. AVE cells halt upon reaching the adjoining region of VE overlying the extra-embryonic ectoderm, which displays reduced neighbour exchange and in which Dvl2 is excluded specifically from the plasma membrane. Though a single continuous sheet, these two regions of VE show distinct patterns of F-actin localisation, in cortical rings and an apical shroud, respectively. We genetically perturb PCP signalling and show that this disrupts the localisation pattern of Dvl2 and F-actin and the normal migration of AVE cells. In Nodal null embryos, membrane localisation of Dvl2 is reduced, while in mutants for the Nodal inhibitor Lefty1, Dvl2 is ectopically membrane localised, establishing a role for Nodal in modulating PCP signalling. These results show that the limits of AVE migration are determined by regional differences in cell behaviour and protein localisation within an otherwise apparently uniform VE. In addition to coordinating global cell movements across epithelia (such as during convergence extension), PCP signalling in interplay with TGFβ signalling can demarcate regions of differing behaviour within epithelia, thereby modulating the movement of cells within them.